1999
DOI: 10.1098/rspb.1999.0779
|View full text |Cite
|
Sign up to set email alerts
|

Do female great tits (Parus major) assess males by eavesdropping? A field study using interactive song playback

Abstract: Male singing behaviour correlates with extra-pair success in several passerine birds. Singing interactions during territorial contests provide relative information on the males involved. Such information may be important in female extra-pair behaviour and eavesdropping on singing interactions among males may allow females to make such relative assessments. We used interactive playback to instigate singing contests with male great tits during the peak fertile period of their mate in an attempt to alter females'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
146
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(152 citation statements)
references
References 25 publications
3
146
1
2
Order By: Relevance
“…Females can acquire public information on a prospective mate in two distinct ways. They may observe prospective mates in intra-sexual aggressive contests (Doutrelant and McGregor, 2000;Otter et al, 1999). For example, in female black-capped chickadees, Poecile atricapillus, the probability of extra-pair copulations depends on the outcome of male-male vocal contests.…”
Section: S Castellano Et Al / Behavioural Processes XXX (2012) Xxx-xxxmentioning
confidence: 99%
“…Females can acquire public information on a prospective mate in two distinct ways. They may observe prospective mates in intra-sexual aggressive contests (Doutrelant and McGregor, 2000;Otter et al, 1999). For example, in female black-capped chickadees, Poecile atricapillus, the probability of extra-pair copulations depends on the outcome of male-male vocal contests.…”
Section: S Castellano Et Al / Behavioural Processes XXX (2012) Xxx-xxxmentioning
confidence: 99%
“…The emphasis that this puts on information gathering by 'eavesdropping' has had important implications for empirical studies of male-male assessment and mate choice (e.g. Otter et al 1999). However, applying a communication networks approach to longdistance signalling also has consequences for studies of social recognition.…”
Section:  2000 the Association For The Study Of Animal Behaviourmentioning
confidence: 99%
“…Furthermore, observations of singing in songbird neighborhoods reveal that the interactive communication is usually an ongoing process that lasts throughout the breeding season, and that birds may use direct interaction as well as eavesdropping on other interactions to continually adjust their assessment of the status of their neighbors. For example, recent field experiments on songbirds have shown that males make decisions concerning whom to challenge and females make decisions concerning whom to mate with based on information acquired by eavesdropping on singing interactions (Naguib & Todt, 1997;Otter et al, 1999;Mennill et al, 2002). In the species studied to date, song overlapping, song-type matching, frequency matching, and/or song leading seem to be some of the critical cues that indicate relative status between two singers (Mennill & Ratcliffe, 2004;Peake et al, 2005;Kunc et al, 2006).…”
mentioning
confidence: 99%